Effect of Using Compressed Stabilized Earth Blocks on the Thermal comfort in Architectural Spaces: أثر استخدام وحدات البناء من التربة المثبتة المضغوطة على الراحة الحرارية داخل الفراغات المعمارية - Osama Ahmed Ibrahim Masoud - Dina Mahmoud Sadiq - Mohamed Ibrahim Mohamed Abdel Hadi - Ayman Sayed Mohamed Ahmed (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2019)
The problem of high building materials prices, using traditional building systems, consumes a great deal of energy during manufacturing or operating the facility. Accordingly, many researchers have been taken out recently to find alternatives traditional building systems and materials such as Compressed Stabilized Earth Blocks, which relates on using available natural soil compressed at high pressure, This research aims to evaluate the effect of Compressed Stabilized Earth Blocks as alternative walls for walls made from traditional blocks on thermal comfort in architectural spaces through using (Design builder) for defining energy consumption. Two types of natural soils were used (Sandy soil and Silty soil) and a partial replacement was made to the used soil types by utilizing some materials Aswan clay and Clay soil in order to improve soil performance then adding 8% cement of the total weight for stabilizing the mix. Building blocks were made of best 8 mixes in order to achieve the requirements of Egyptian Code for building by Stabilized Earth Blocks. This study is conducted on a residential sample (Social Housing sample composed of two residential units with a total area of 90 m2 for each) for comparison between building blocks made from stabilized soil and other blocks made from local brick units. Experimental results shown that the usage of building blocks, made from stabilized soil with 8% cement, helps to reduce energy consumption in order to achieve thermal comfort ranging from 5% to 25%, compared with other brick types. It also helps to reduce resources and energy consumption used in manufacturing and to decrease negative environmental impacts resulting from other building materials. Research recommendations refer to the necessity of using soil in producing building blocks in new projects under design for choosing best usage of soil and stabilize it in order to benefit from natural materials, rationalize electric power consumption in buildings